Factors Affecting Stunting in Toddlers in Lesluru Village and Kuralele Village, Teon Nila Serua District, Central Maluku Regenct - Sanora L D Parhusip; Erynola Moniharapon; Sophia G Sipahelut (Jurnal Agrosilvopasture-Tech, 2023)
Stunting is a condition where there is to thrive in children under five years old due to chronic malnutrition that children are too short for their age. The purpose of this study was to determine the factors that influence the incidence of stunting in toddlers in Teon Nila analysis. Based on the results of the study it can be concluded as follows: There is a relationship between factors of mother's education, age of marriage, number of children, and feasibility of latrines with the incidence of stunting in children under five in Teon Nila Serua District, on the contrary, there is no relationship between factors of drinking water facilities, livable houses and food consumption varies with the incidence of stunting in children under five in Village Lesluru and Village Kuralele Teon Nila Serua District.